2019
DOI: 10.1002/hrdq.21342
|View full text |Cite
|
Sign up to set email alerts
|

The double‐edged sword of coaching: Relationships between managers' coaching and their feelings of personal accomplishment and role overload

Abstract: Attention to the effects of managerial coaching usually focuses on subordinates. However, knowledge of the impact of coaching on the coaches is limited. Drawing upon conservation of resources theory, this study examined the extent to which coaching has benefits and costs for managers who spend time and energy coaching their subordinates. Structural equation modeling results from a multisource, time-lagged survey showed that managerial coaching rated by team members affected managers' self-ratings of job attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 102 publications
(169 reference statements)
2
33
0
Order By: Relevance
“…Prior studies have indicated that perceptions of organizational support can be fostered by rendering fair decisional policies, maintaining open channels of communication with employees ( Eisenberger and Stinglhamber, 2011 ), assuring employees that their jobs are secure, offering valuable training or developmental programs that promote employees’ personal growth, and eliminating continual work overloads ( Rhoades and Eisenberger, 2002 ). Thus, organizations should care about employees’ well-being, value their contributions, and be willing to help employees when they need a favor ( She et al, 2019 ). On the other hand, managers should support their subordinates, for instance, by having regular meetings with them, resolving any conflicting job responsibilities, or providing them with the materials or emotional resources they need (e.g., Eisenberger and Stinglhamber, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have indicated that perceptions of organizational support can be fostered by rendering fair decisional policies, maintaining open channels of communication with employees ( Eisenberger and Stinglhamber, 2011 ), assuring employees that their jobs are secure, offering valuable training or developmental programs that promote employees’ personal growth, and eliminating continual work overloads ( Rhoades and Eisenberger, 2002 ). Thus, organizations should care about employees’ well-being, value their contributions, and be willing to help employees when they need a favor ( She et al, 2019 ). On the other hand, managers should support their subordinates, for instance, by having regular meetings with them, resolving any conflicting job responsibilities, or providing them with the materials or emotional resources they need (e.g., Eisenberger and Stinglhamber, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, by identifying the moderating role of POS, we address recent calls to clarify its influence as a protective factor against resource loss and fatigue ( She et al, 2019 ) and in promoting an organizational environment where employees can engage in OCB in a way that maximizes its positive aspects and minimizes it negative aspects ( Garcia et al, 2021 ). We demonstrate that POS can weaken the curvilinear relationship between OCB and citizenship fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although having managers with coaching expertise who can enact managerial coaching behaviors is becoming increasingly important, research that concentrates on managers who coach is less prevalent in the literature (McCarthy and Milner, 2020;She et al, 2019). Of the limited literature that has examined managers who coach, promising lines of inquiry have focused on the catalysts or triggers that influence managers to coach (Amy, 2008;Ellinger, 2003;Turner and McCarthy, 2015;Campbell and Evans, 2016), and the belief systems that guide managers to adopt coaching roles and enact coaching behaviors (Adele, 2019;Anderson, 2013;Campbell and Evans, 2016;Ellinger and Bostrom, 2002;Hunt and Weintraub, 2002, 2011, 2017Misiukonis, 2011).…”
Section: Strategic Leadership For Learningmentioning
confidence: 99%
“…Sense of self-worth is an individual’s subjective feeling after evaluating himself, that is, “human” subjective evaluation, 18 and sense of role overload is an individual’s subjective feeling after evaluating his work, that is, “work situation” subjective evaluation. 19 In other words, perceived trust may stimulate employees’ positive self-evaluation, and also can cause employees’ negative evaluation of sense of role overload. Therefore, this paper starts from employees’ evaluation perception of trust and discusses how employees’ perception of trust affects proactive behavior through sense of self-worth and job sense of role overload, and clarifies the whole picture of employees’ behavior with perceived trust.…”
Section: Introductionmentioning
confidence: 99%